Comparison of local cryotherapy and sonotherapy effectiveness in the treatment of gonarthrosis symptoms - Agata Bloch; Małgorzata Kordowska; Ewa Frankiewicz; Krystian Kałużny; Anna Kałużna; Magdalena Hagner-Derengowska; Walery Zukow (Kazimierz Wielki University, 2018)
The aim of this study was comparison of local cryotherapy and sonotherapy effectiveness in the treatment of gonarthrosis symptoms. Material and methods: The studies on the comparison of local cryotherapy and sonotherapy effectiveness were conducted in a research group of one hundred people singled out from the patients staying at the Wieniec Zdrój Sanatorium in Wieniec Zdrój. Before the series of sonotherapy and cryotherapy treatments and after their completion, all patients were assessed using: Centimeter tape, Goniometer, VAS (Visual Analog Scale), Laitinen Questionnaire and Sit-up Test. Results: After the rehabilitation, the intensity of pain was determined at 4.45 points, on a scale from 0 to 8 points. The intensity of pain in the VAS scale among respondents decreased significantly by 1.750 points. The average pain intensity was 1.40 points (SD = 0.778), which resulted in a significant change in the form of pain relief (p = 0.580). The frequency of pain ranges from 0 to 4 points (M = 1.35). The frequency of its occurrence decreased significantly (p = 0.670). After rehabilitation, the frequency of analgesics was on average 0.66 points, and the limit on physical activity was 1.40 points (p = 0.520). The limitation of physical activity was determined on average at the level of 1.04 points, which reduced its limit by 0.560 points. After rehabilitation, the range of motion in the knee joint increased to 99.60 °. On average, the range of movement of patients in the knee joint after rehabilitation increased by -1.429 °. After rehabilitation, knee circumference of the kneecap was between 30 cm and 76 cm. The average result was 42.375 cm and decreased significantly by 0.1676 cm. The circumference of the knee joint above the kneecap oscillated between 28 - 80.5 cm (D = 44.335 cm), which gave the effect of reducing the edema by 0.320 cm. The treatments performed varied only the results in the frequency of analgesics (p = 0.45). Better effects occurred in patients undergoing sonotherapy (M = 0.048) than in cryotherapy (M = 0.84). Conclusions: Local cryotherapy and sonotherapy reduces the severity and frequency of pain and reduces swelling in the knee joints. Positive effects of therapy reduce the amount of analgesics used. However, better results are obtained in patients undergoing sonotherapy than in cryotherapy. In addition, the range of flexion movements of the knee joints is increased under the influence of treatments. There are significant differences in the improvement of the range of motion among patients treated with sonotherapy than cryotherapy.